Foreword - Elena Buglova (International Journal of Nuclear Security, 2022)
The commitment to achieving nuclear security globally needs the efforts of both men and women, as diversity and gender equality bring benefits to all fields. However, women are underrepresented in nuclear security, as well as in the nuclear field in general, so it is important to understand and tackle the barriers that women can face to joining and thriving in the field, and I believe this special issue of the International Journal of Nuclear Security (IJNS) on Women in Nuclear Security will help in this regard.